Community-scale baseload generation from marine energy. (15th December 2019) - Soudan, Bassel
Abstract: While significant work has been done on the use of solar and wind energy as sources of renewable generation, marine energy is only recently receiving serious consideration. This work investigates the prospects of generating electrical power by harnessing the energy inherent in the seas and oceans. Here we examine the possibilities for community-scale off-grid distributed base power generation from marine energy with application to electrically deficient coastal communities in underdeveloped regions. The potentials for wave, tidal stream, and tidal range resources are discussed. The different hydrodynamic-to-mechanical energy conversion schemes are evaluated for appropriateness to the target application. Energy extraction and power-take-off technologies along with generation control strategies are also evaluated. In the end, recommendations are produced for the appropriate system that can address the needs of the intended setup. Highlights: Some of the most electrically disenfranchised populations live within short distance of major bodies of water. The article proposes a baseload generation off-grid system design for an underdeveloped coastal community. The article investigates options for energy converters, power take-off technologies, as well as control strategies. We propose a setup comprised of a direct-driven rotary generator atop a vertical Gorlov helical-blade cross-flow turbine.